Ejection phase indices of left ventricular performance in infants, children, and adults. Issue 2 (February 1975) - Tynan, M; Reid, D S; Hunter, S; Kaye, H H; Osme, S; Urquhart, W; Davies, P
Abstract : A validatory study of quantitative single plane left ventricular cineangiography is presented, using human left ventricular casts ranging in size from 1.6 to 135 ml. Good correlation was found between actual and calculated volumes (r=0.967). 62 patient studies were carried out and the value of the usually calculated indices of left ventricular performance were compared to one another. Ejection fraction and mean rate of circumferential fibre shortening (mean Vcf) were found to be the best discriminators of abnormal left ventricular function, and, on the basis of the presented data, it is suggested that mean Vcf is the more sensitive index of left ventricular performance.